Analisis Usaha Penggemukan Sapi Potong di Kabupaten Bintan: Agribisnis peternakan - Eko Sutrisno; Sumiati (Universitas Pasir Pengaraian, 2024)
The high price of local beef in Bintan Regency is influenced by the increase in production prices which includes the purchase of livestock seeds and animal feed. This causes the input costs for beef cattle production in Bintan Regency to increase drastically. Based on these problems, it is necessary to know the production costs that must be incurred by farmers in running a beef cattle fattening business in Bintan Regency. The aim of the research is to analyze the beef cattle fattening business in Bintan Regency. The research was conducted in four sub-districts in Bintan Regency. The research sample was breeders who run beef cattle farms with a minimum of 5 cows kept in a pen and have been running their business for the last 5 years. The sampling technique uses purposive sampling. The data obtained is analyzed to calculate production costs, production quantities, profits and business efficiency. The research results show that the average production costs incurred by farmers are IDR 88,754,960, income is IDR 121,137,603 and profits are IDR 32,382,643, so the R/C return cost ratio is 1.36. Meanwhile, the production cost of 1 cow is IDR 17,258,008 with a selling price of IDR 22,025,019 resulting in a profit of IDR 4,767,011